A Call to Action: Maine’s Colleges and Universities Respond to an Aging Population - Hecker, Jeffrey; Gugliucci, Marilyn (Maine Policy Review, 2015)
Jeffrey E. Hecker and Marilyn R. Gugliucci report on the findings of the Higher Education Workgroup, which is part of the Maine Aging Initiative. They present summary information on aging-related research, gerontology/geriatrics educational curricula, and educational opportunities for older adults including retooling for employment.
Keywords: aging; Maine Aging Initiative; aging-related research; senior college; Maine; workforce education